Green-synthesised silver nanoparticles: antibacterial activity and alternative mechanisms of action to combat multidrug-resistant bacterial pathogens: a systematic literature review - Abayeneh Girma; Getachew Alamnie; Tigabu Bekele; Gedefaw Mebratie; Bawoke Mekuye; Birhanu Abera; Dereba Workineh; Abay Tabor; Debela Jufar (Green Chemistry Letters and Reviews)
Antimicrobial resistance (AMR) is the top global public health and development threat. It has led to 4·95 million deaths associated with bacterial AMR in 2019, including 1·27 million deaths attributable to bacterial AMR. In addition to causing death and disability, it is projected that by 2030, the annual gross domestic product (GDP) losses due to AMR could range from US$1 trillion to US$3.4 trillion. In the current study, bio-capped silver nanoparticles (AgNPs) showed significant antibacterial activities against both gram-positive and gram-negative MDR bacterial pathogens. 2.50 μg/ml to 100 mg/ml and 3.8 μg/ml to 2.5 mg/ml were the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of AgNPs, while the zone of inhibition (ZOI) was 4 to 25 mm. Particle size, shape, type of capping or stabilizing agent, surface charge, pH, exposure time, concentration, and bacterial type affect the antibacterial activities of AgNPs. Cell wall and membrane damage, destruction of biomolecules (lipids, proteins, and DNA), disruption of the electron transport chain, and proton motive force are mechanisms of action of AgNPs. In general, green-synthesised AgNPs from plants and bacteria (synergistic effect between AgNPs and natural compounds) displayed significant antibacterial activity against a wide range of Gram-positive and Gram-negative MDR bacteria.